Glycoprotein N subtypes of human cytomegalovirus induce a strain-specific antibody response during natural infection - Burkhardt, Christiane; Himmelein, Susanne; Britt, William; Winkler, Thomas; Mach, Michael (Journal of General Virology, 2009)
Human cytomegalovirus (HCMV) encodes several highly polymorphic envelope glycoproteins; however, the biological relevance of this polymorphism is unclear. Glycoprotein N (gN) is one member of this polymorphic protein family. Four major gN genotypes (gN1-4) have been identified. We have tested the hypothesis that the gN polymorphism represents a mechanism to evade a neutralizing antiviral antibody response. Four recombinant viruses that differed only in the expression of the gN genotype were constructed on the genetic background of HCMV strain AD169. Exchange of gN genotypes had a minor detectable influence on virus replication, gN expression and gN-gM complex formation. Randomly selected human sera were analysed for neutralizing activity against the recombinant viruses. Of these, 70% showed no difference in neutralizing titre between the viruses, whereas 30% showed strain-specific neutralization. Differences in 50% neutralization titre reached >8-fold. Viruses expressing the gN4 genotype were neutralized significantly better than those expressing the other gN genotypes. Strain specificity, or lack thereof, could not be attributed to the presence or absence of anti-gN antibodies, as all sera contained antibodies reacting with gN (as determined by ELISA). Thus, polymorphism of gN could contribute to evasion of an efficient neutralizing-antibody response and facilitate reinfection in previously seropositive individuals. © 2009 SGM.